External Cervical Resorption Detected by Cone Beam Computed Tomography on an Immature, Unerupted Maxillary Second Premolar - Karen Berrigan; Bradly Gettleman; Sabita Rao; Janet Jordan; Mark Stieg; Lawrence Johns (Case Reports in Dentistry)
Root resorption is a commonly recognized risk of orthodontic treatment and can range from minimal changes at the apex to aggressive and extensive erosion of tooth structure. The following report is aimed at presenting a rare case of idiopathic aggressive preeruptive root resorption in a maxillary second premolar of a young child prior to orthodontic force. During phase I orthodontic treatment, the maxillary premolar required surgical exposure with a bracket and chain to assist in its eruption. Before the exposure, a cone beam computed tomography (CBCT) was captured to aid in localizing the premolar and its relationship to vital structures. In addition to identifying relevant anatomy, the image also revealed an incidental finding of extensive external cervical root resorption. The risks, benefits, prognosis, and alternatives of continuing with surgical exposure of the affected premolar were presented to the guardian. The informed and consented decision was made to continue with the exposure and subsequent orthodontic treatment to align the tooth in the arch. Upon eruption to the occlusal plane, the tooth was amenable to endodontic pulp vitality testing, Endo Ice, and a follow-up CBCT. It was determined that there was advanced aggressive progression of the resorptive process. The Patel Classification 3Cd/Class 4 Heithersay ECR diagnosis and a poor prognosis ultimately resulted in the extraction of the tooth. Management of this case highlights a number of important clinical features including the rarity of advanced preeruptive idiopathic external cervical root resorption, a multidisciplinary approach (orthodontic, endodontic, and surgical) to diagnose and manage the ECR, and the importance of prescribing and acquisition of appropriate imaging to aid in the early diagnosis of the entity. This case report will add to the body of knowledge of a rare incidence of advanced ECR on a young patient with a nontraumatized, unerupted maxillary second premolar.